2020
DOI: 10.1002/mnfr.202000284
|View full text |Cite
|
Sign up to set email alerts
|

Propagule Powder of Japanese Yam (Dioscorea Japonica) Reduces High‐Fat Diet‐Induced Metabolic Stress in Mice through the Regulation of Hepatic Gene Expression

Abstract: Scope Japanese yam propagules are supposed to have high potential as a functional food. However, there are almost no studies examining their physiological function. This study aims to elucidate the physiological function of Japanese yam propagules that are heated, freeze‐dried, and powdered. Methods and results A high‐fat diet with Japanese yam propagules is administered to mice for 4 weeks. High‐fat loading induces a decline in respiratory quotient, and a high‐fat diet with propagules reduces it more. This re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
(37 reference statements)
0
3
0
Order By: Relevance
“…KEGG analysis of the detected gut microbiota revealed that carbohydrate, amino acid, and lipid metabolism were dominantly enriched metabolic pathways after different treatments. Long-term HFD could suppress gluconeogenesis, promote glycolysis [54], and thus affect carbohydrate metabolism, whereas FLT or FBT administration reversed this state to some extent. Imbalances in amino acid metabolism caused by HFD can result in various health problems.…”
Section: Flt and Fbt Exerted Anti-obesity Effects By Maintaining The ...mentioning
confidence: 99%
“…KEGG analysis of the detected gut microbiota revealed that carbohydrate, amino acid, and lipid metabolism were dominantly enriched metabolic pathways after different treatments. Long-term HFD could suppress gluconeogenesis, promote glycolysis [54], and thus affect carbohydrate metabolism, whereas FLT or FBT administration reversed this state to some extent. Imbalances in amino acid metabolism caused by HFD can result in various health problems.…”
Section: Flt and Fbt Exerted Anti-obesity Effects By Maintaining The ...mentioning
confidence: 99%
“…Modern studies have confirmed that the extract species from the fruits, leaves, and flowers of C. pinnatifida had a variety of Table 3 Name, type and sources of active components in FMH with ability to regulate blood lipids biological and pharmacological activities, including protection against cardiovascular disease, lipid-lowering and antioxidant activities. Compounds 10 and 11 were obtained from C. pinnatifida and regulated lipid metabolism by regulating the absorption, synthesis, and metabolism of triglycerides and cholesterol [16,17] . Compound 14 from D. opposita could ameliorate hypercholesterolemia by improving lipid composition, and reducing oxidative stress [18] .…”
Section: Triterpenoids and Their Glycosidesmentioning
confidence: 99%
“…For carbohydrate metabolism, the propagules inhibit glycolysis and glycogen synthesis and promote gluconeogenesis. In summary, the propagules regulate fat metabolism and carbohydrate metabolism to inhibit disorders of carbohydrate and fat metabolism in high fat-loaded mice [ 92 ].…”
Section: Prevention and Treatment Of Metabolic Diseasesmentioning
confidence: 99%